2004
DOI: 10.5194/aab-47-211-2004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of calf rearing methods and milking methods on performance traits of crossbred dairy cattle in Thailand – 1. Milk yield and udder health

Abstract: Forty crossbred (75-87.5% HF) dairy cows were included in a 2 x 2 factorial experiment composed of hand milking (HM) or machine milking (MM), and artificial rearing (bucket feeding, BR) or restricted suckling (RS). Calf suckling and milk feeding was done until 84 days postpartum. Milking was continued until the end of lactation. MM cows had a significantly (p<0.05) higher daily saleable milk production (SMP) (7.49 vs. 6.97 kg/day), daily total milk production (TMP) (8.60 vs. 7.96 kg/day) and total lactation mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…However, further research needs to be done to clearly establish the amount of milk fed to the kids in order to ascertain the effectiveness of the rearing system in terms of net saleable milk yield. Studies done in cattle show that application of restricted suckling improves milk yield (and, therefore, saleable milk), increases lactation milk yield and maintains the condition of the dam (udder health) than bucket feeding (Boonbrahm et al 2004;Fröberg et al 2007). …”
Section: Discussionmentioning
confidence: 98%
“…However, further research needs to be done to clearly establish the amount of milk fed to the kids in order to ascertain the effectiveness of the rearing system in terms of net saleable milk yield. Studies done in cattle show that application of restricted suckling improves milk yield (and, therefore, saleable milk), increases lactation milk yield and maintains the condition of the dam (udder health) than bucket feeding (Boonbrahm et al 2004;Fröberg et al 2007). …”
Section: Discussionmentioning
confidence: 98%
“…Suckling twice daily as opposed to unrestricted suckling has a lower effect on reproductive performance (EDMUND, 1977). The possible cause of poor reproductive performance among RS cows could also be related to a nutritional effect, as cows which yield more milk would be expected to have less nutrients available for reproduction, as reported by WILTBANK (1970), BUTLER and SMITH (1989), TERQUI et al (1982) and TERVIT et al (1977). However, SHORT et al (1972) andMEJIA et al (1998) showed that suckling increased the postpartum anoestrus interval independently of nutrient intake.…”
Section: Discussionmentioning
confidence: 96%
“…Calf rearing management included bucket rearing of calves (BR), and restricted suckling (RS) for 15 minutes post milking until 84 th day postpartum. A detailed description of experimental procedures is provided in BOONBRAHM et al, 2004. Observations for oestrus signs (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In ewes, McKusick et al (2002a) stated that the cisternal milk fat but not milk protein percentage was lower than in alveolar milk (4.49 % vs. 7.92 %). The suckled cows do not release all of their milk during machine milking, so that the low fat percentage can be partly attributed to the fact that it is only part of the milk stored in the cistern (Boonbrahm et al 2004a). Levy (1964) observed a decrease of about 90 % of fatty acid synthesis in rats by 24h of weaning.…”
Section: Resultsmentioning
confidence: 99%
“…Early separation of the calf from the cow is the basis of the modern industry, but the cow-calf rearing system is useful in organic and ecological farms where healthy rearing and production is required. There are a number of studies reporting on higher weight gains during the suckling period for restricted suckling calves compared to the artificial rearing system (Fallon & Harte 1980, Boonbrahm et al 2004a, 2004b, Shamay et al 2005, Fröberg et al 2007. Bar-Pelled et al (1997) reported on a better cow and calf health for the nursing system, higher height at the withers, an earlier age at calving and a tendency towards higher milk production during the first lactation.…”
Section: Introductionmentioning
confidence: 99%